Normalising the conversation: a qualitative analysis of player and stakeholder perceptions of menstrual health support within elite female soccer. Issue 5 (1st December 2022) - McHaffie, Samuel J.; Langan-Evans, Carl; Morehen, James C.; Strauss, Juliette A.; Areta, José L.; Rosimus, Christopher; Evans, Martin; Elliott-Sale, Kirsty J.; Cronin, Colum J.; Morton, James P.
ABSTRACT: Purpose: This qualitative study explores player and stakeholder perceptions of menstrual health support in elite female soccer. Methods: Semi-structured interviews were conducted with 47 participants including players (n = 12), parents (n = 9), coaches (n = 9), sport scientists (n = 7), nutritionists (n = 5) and medical staff (n = 5). Results: Via thematic analysis, data demonstrate that elite female soccer players experience a range of physical and psychological symptoms primarily at the onset of and during menses (as also perceived by stakeholders), with most participants perceiving these symptoms to impact performance. Nonetheless, menstrual health support is perceived as minimal and although players have their menstrual status tracked, they report little understanding as to why or how this information is used. This confusion was also present among stakeholders, often as a result of uncertainty about the evidence supporting the need for menstrual health support. The perceived lack of support may also be reflective of a culture where conversations about the menstrual cycle are not normalised. Overall, this may result in failure to identify and treat menstrual irregularities despite non-coaching staff members perceiving them to be common amongst players. Conclusion: These data support the need for individualised support based on the lived experiences of individual players and support staff. Furthermore, our research identifies the need for organisational, stakeholder, and player centred education programmes (led by experts in female athlete health) that create an environment where players receive personalised menstrual health support.